The relationship between cognitive control and posttraumatic stress symptoms - Bomyea, Jessica (2011)
BACKGROUND AND OBJECTIVES: Recently researchers have theorized that individual differences in cognitive control (i.e., the ability to complete goal-directed behavior by actively maintaining information while inhibiting irrelevant information) may elucidate processes involved in disorders characterized by intrusive thoughts and memories. By this account, the relationship between cognitive control and emotional disorders would be specific to symptoms associated with intrusive cognitions, such as re-experiencing symptoms of posttraumatic stress disorder (PTSD). METHODS: In the present study, 77 undergraduate participants with a self-reported history of trauma exposure were administered assessments of cognitive control (working memory capacity; WMC), PTSD symptoms, trait anxiety, and depression. PTSD symptoms from each of the three symptom clusters (re-experiencing, avoidance, and hyperarousal) were predicted from trait anxiety, depression, and WMC performance scores using separate regression models. RESULTS: After controlling for trait anxiety and depression, there was a negative, statistically significant relationship between cognitive control and re-experiencing symptoms but not avoidance or hyperarousal symptoms. LIMITATIONS: The study was completed cross-sectionally and did not include a diagnostic assessment of PTSD. CONCLUSIONS: Findings add to extant literature suggesting a relationship between cognitive control and intrusive cognitions. Moreover, the present study expands the current literature by demonstrating the specificity of this relationship within individuals with varying degrees of PTSD symptom severity.